A novel salt- and organic solvent-tolerant phosphite dehydrogenase from Cyanothece sp. ATCC 51142 - Abdel-Hady, Gamal Nasser; Tajima, Takahisa; Ikeda, Takeshi; Ishida, Takenori; Funabashi, Hisakage; Kuroda, Akio; Hirota, Ryuichi (Frontiers in Bioengineering and Biotechnology, 2023)
Phosphite dehydrogenase (PtxD) is a promising enzyme for NAD(P)H regeneration. To expand the usability of PtxD, we cloned, expressed, and analyzed PtxD from the marine cyanobacterium Cyanothece sp. ATCC 51142 (Ct-PtxD). Ct-PtxD exhibited maximum activity at pH 9.0 and 50°C and high stability over a wide pH range of 6.0-10.0. Compared to previously reported PtxDs, Ct-PtxD showed increased resistance to salt ions such as Na + , K + , and NH4 + . It also exhibited high tolerance to organic solvents such as ethanol, dimethylformamide, and methanol when bound to its preferred cofactor, NAD + . Remarkably, these organic solvents enhanced the Ct-PtxD activity while inhibiting the PtxD activity of Ralstonia sp. 4506 (Rs-PtxD) at concentrations ranging from 10% to 30%. Molecular electrostatic potential analysis showed that the NAD + -binding site of Ct-PtxD was rich in positively charged residues, which may attract the negatively charged pyrophosphate group of NAD + under high-salt conditions. Amino acid composition analysis revealed that Ct-PtxD contained fewer hydrophobic amino acids than other PtxD enzymes, which reduced the hydrophobicity and increased the hydration of protein surface under low water activity. We also demonstrated that the NADH regeneration system using Ct-PtxD is useful for the coupled chiral conversion of trimethylpyruvic acid into L-tert-leucine using leucine dehydrogenase under high ammonium conditions, which is less supported by the Rs-PtxD enzyme. These results imply that Ct-PtxD might be a potential candidate for NAD(P)H regeneration in industrial applications under the reaction conditions containing salt and organic solvent.